Raising Healthy Children: Age Three - Rebecca A. Clinton; Karla P. Shelnutt (EDIS)
FCS8890, a 3-page illustrated fact sheet by Rebecca A. Clinton and Karla P. Shelnutt, provides general guidelines for parents of three-year old’s in nutrition, physical activity, and developmental milestones. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2010.